1996
DOI: 10.1046/j.1365-2141.1996.d01-1734.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant cytotoxic donor T‐cell activity specific to patient HLA class I antigens correlating with mortality after unrelated BMT

Abstract: Unrelated bone marrow transplantation (BMT) is associated with increased post-transplant complication rates, partly because more transplantation antigens are mismatched than in HLA-identical related BMT. We have shown previously that the cytotoxic T-lymphocyte precursor (CTLp) test performed before transplantation specifically detects HLA class I mismatches demonstrating its usefulness for the identification of new HLA class I alleles. In this study we analysed the clinical relevance of the CTLp test in 41 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…IFN-gP f was also associated with aGVHD in patients receiving BMT from HLA-identical siblings, but not in those receiving BMT from MUD. Similar results have been reported by others [19][20][21][22][23][24][25][26] and our group, 27 and the present study demonstrated some interesting findings that might be of clinical importance. First, although HTLP f /CTLP f were associated with aGVHD in general, some patients with high HTLP f /CTLP f did not develop severe aGVHD, whereas others who develop aGVHD had low HTLP f /CTLP f levels.…”
Section: Discussionsupporting
confidence: 81%
“…IFN-gP f was also associated with aGVHD in patients receiving BMT from HLA-identical siblings, but not in those receiving BMT from MUD. Similar results have been reported by others [19][20][21][22][23][24][25][26] and our group, 27 and the present study demonstrated some interesting findings that might be of clinical importance. First, although HTLP f /CTLP f were associated with aGVHD in general, some patients with high HTLP f /CTLP f did not develop severe aGVHD, whereas others who develop aGVHD had low HTLP f /CTLP f levels.…”
Section: Discussionsupporting
confidence: 81%
“…[28][29][30] It recogmismatches and for one patient due to advanced disease nizes mismatches for class I, including HLA-C alleles, and status.…”
Section: Search Outcome For Patients From Non-european Originmentioning
confidence: 99%
“…Quantitation of allospecific T-cell precursors, using limiting dilution based assays (LDA; cytotoxic T lymphocyte precursor [CTLp] and helper T lymphocyte precursor) (8,9), have all been used to assess the in vitro allogeneic potential of HLA mismatches (10)(11)(12)(13)(14)(15)(16)(17). However, the correlation between the quantitation of allospecific T-cell precursor frequencies and incidences of graft rejection or GvHD has been disappointing and laboratory-dependent (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%